(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This study assessed the accuracy of torque, tip, rotation, and intra-arch movements achieved by passive self-ligating lingual straight-wire appliances with square-slot brackets in 25 adult Caucasian patients (16 females, 9 males; mean age 26.5 ± 4.3 years) with Class I or mild Class II malocclusion. Treatment involved orthodontic procedures using ALIAS appliances (Ormco, Orange, CA) without extractions. Digital models at pre-treatment (T0), planned (T1), and achieved (T2) stages were analysed using an intraoral scanner (Medit I500, iScan Medit, Seoul, Korea). Angular values (torque, tip, rotation) and linear intra-arch widths were measured using VAM software (Vectra, Canfield Scientific, Fairfield, NJ, USA). Statistical analysis included Student’s t-test and Friedman test (p < 0.05). The mean accuracy of angular values was 77.25 ± 7.71% for torque, 78.41 ± 6.17% for tip, and 77.99 ± 6.58% for rotation. Significant differences were observed between planned and achieved movements across all tooth groups, arches, and overall dentition (p < 0.001). Anterior sectors showed higher accuracy in intra-arch diameters (83.54 ± 5.19% for maxillary inter-canine distance) compared to posterior sectors (67.28% for maxillary inter-second molar distance). In conclusion, passive self-ligating lingual straight-wire appliances with square-slot brackets demonstrate clinically satisfactory accuracy, albeit with a decrease in accuracy from anterior to posterior sectors.